Effects of Essential Fatty Acids during In Vitro Maturation of Porcine Oocytes: Hormone Synthesis and Embryonic Developmental Potential - Kang-Sig Kim; Hum-Dai Park (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Omega-3 α-linolenic acid and omega-6 linoleic acid are essential fatty acids for health maintenance of human and animals because they are not synthesized in vivo. The purpose of this study was to evaluate the effect of α-linolenic acid and linoleic acid supplementation on in vitro maturation and developmental potential of porcine oocytes. Various concentrations of α-linolenic acid and linoleic acid were added into in vitro maturation medium, and we evaluated the degree of cumulus expansion, oocyte nuclear-maturation rate, blastocyst rate, blastocyst quality, and levels of prostaglandin E2, 17b-estradiol, and progesterone in the spent medium. High doses (100 μM) of α-linolenic acid and linoleic acid supplementation significantly inhibited cumulus expansion and oocyte nuclear maturation, and prostaglandin E2 synthesis also significantly decreased compared with other groups (p < 0.05). Supplementation of 50 μM α-linolenic acid and 10 μM linoleic acid showed higher quality blastocysts in terms of high cell numbers and low apoptosis when compared with other groups (p < 0.05), and synthesis ratio of 17b-estradiol / progesterone also significantly increased compared with control group (3.59 ± 0.22 vs. 2.97 ± 0.22, 3.4 ± 0.28 vs. 2.81 ± 0.19, respectively; p < 0.05). Our results indicated that supplementation with appropriate levels of α-linolenic acid and linoleic acid beneficially affects the change of hormone synthesis (in particular, an appropriate increase in the 17b-estradiol / progesterone synthesis ratio) for controlling oocyte maturation, leading to improved embryo quality. However, high doses of α-linolenic acid and linoleic acid treatment results in detrimental effects.